1997
DOI: 10.1093/emboj/16.14.4456
|View full text |Cite
|
Sign up to set email alerts
|

Why is the initiation nick site of an AT-rich rolling circle plasmid at the tip of a GC-rich cruciform?

Abstract: curious accident of sequence organization but has a Medical School, New York, NY 10016, USA substantive biological rationale that is derived from the 1 Corresponding author plasmid's need to prevent recycling of the initiator because recycling would obviate control of plasmid copy number. pT181 and other closely related rolling circle plasmidsRecycling is prevented by a modification of the initiator, have the nicking site for initiation of replication consisting of the attachment to one subunit of a short betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
2
39
1
Order By: Relevance
“…In this instance the dimeric RepC protein facilitates the extrusion of a cruciform in negatively supercoiled DNA followed by site-specific nicking by a topoisomerase-like mechanism in the newly formed loop (28). Structural information on alternative conformations occurring in other replication origins is scarce.…”
Section: Fig 4 Oris* Contains a Hairpin With Partially Single-stranmentioning
confidence: 99%
“…In this instance the dimeric RepC protein facilitates the extrusion of a cruciform in negatively supercoiled DNA followed by site-specific nicking by a topoisomerase-like mechanism in the newly formed loop (28). Structural information on alternative conformations occurring in other replication origins is scarce.…”
Section: Fig 4 Oris* Contains a Hairpin With Partially Single-stranmentioning
confidence: 99%
“…Indeed, it was found that the Rep protein is covalently linked to a small oligonucleotide after a round of replication. This modification prevents it to initiate DNA synthesis and thus ensures that it cannot be reused to start a new round of replication (Rasooly and Novick, 1993;Jin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For this, we utilized oligonucleotide probes containing a 25-bp duplex region and a 28-or 29-nucleotide (nt) ss region at their 5Ј or 3Ј ends (oligonucleotides c and d) ( Table 1). These probes represent the inverted repeat II region from the plasmid pT181 origin in which the sequences present in the 5Ј or 3Ј ss regions can assume a hairpin structure (16,17). The underlined regions in oligonucleotides c and d (Table 1) contain 5ЈCCGG3Ј sequences which (upon intrastrand base pairing) generate a cleavage site for the restriction endonuclease HpaII.…”
Section: Resultsmentioning
confidence: 99%